CD9 expression rivals IDH mutation as a prognostic marker in glioma: a novel nomogram approach - Peng, Yue; Ji, Qiang; Guo, Xiangyu; Zhang, Weichunbai; Yang, Zixuan; Li, Wenbin (Frontiers in Neurology, 2025)
PurposeGlioma remains a lethal malignancy with limited prognostic biomarkers. This study evaluates the prognostic significance and functional mechanisms of tetraspanin CD9 in glioma to establish its clinical relevance and identify therapeutic strategies.MethodsMulti-omics analyses were performed using 1,033 glioma samples from TCGA and CGGA cohorts. A CD9-integrated nomogram was developed via Cox regression. Two-sample Mendelian randomization (MR) assessed the causal link between CD9 expression and glioma risk using IVW, MR-Egger, and WM methods. KEGG enrichment analysis identified biological pathways. Single-cell RNA sequencing from 20 glioblastoma cases was analyzed using CellChat and Monocle3 to explore CD9-mediated cell communication and lineage transitions. Protein-protein interaction (PPI) networks were constructed via STRING and GeneMANIA, and drug predictions were performed using DsigDB.ResultsCD9 overexpression was an independent predictor of poor survival (HR = 1.28, 95% CI 1.03–1.58). The CD9-based nomogram showed high prognostic accuracy (CGGA: C-index = 0.805 ± 0.01, TCGA: C-index = 0.859 ± 0.02). MR confirmed a causal association between CD9 and glioma risk (IVW OR = 1.33, p < 0.05) with no horizontal pleiotropy. CD9 regulated glioma progression via calcium signaling and synaptic pathways, interacting with ITGB1 and CD81. Single-cell analysis revealed CD9-driven NPC-to-OPC transdifferentiation, linked to tumor proliferation. Emetine was identified as a potential CD9-targeting drug.ConclusionCD9 is a prognostic biomarker in glioma, with causal evidence linking its overexpression to tumor development. Its integration into risk models enhances prognostic precision, while drug screening highlights emetine as a potential therapy.